The Impact of COVID-19 on Domestic Tourism by Older People in Taiwan - Chan, Ching-Tang (Frontiers in Public Health, 2022)
Taiwan's older population over the age of 65 was reached about 3.95 million at the end of January 2022, accounting for about 16.9% of the country's total population. It is already an "aged society". With the gradual increase in the older population, the older people tourism market is also getting more and more attention. This article explores how older people tourism is affected by this major international public health event as the COVID-19 epidemic began in Taiwan in early 2020. This study adopts quantitative and PCA method to statistical and analyze the changes and differences before and after the epidemic. The study results can found the frequency of tourism; the number was 5.32, a decrease of 0.77 and at least 1 time tourism decrease of 3.87% after the epidemic. The reasons of not participate tourism; in COVID-19 epidemic factor was 19.90%. The total travel expenses was NT2590, an increase of NT229.67, was not affected by the epidemic. The PCA analysis results of tourism expenses. The first component was food expenses, stay expenses, shopping expenses and others expenses. The factor loadings were 0.989, 0.931, 0.641 and -0.948, respectively. The second component was entertainment expenses and transportation expenses. The factor loadings were 0.997 and 0.902 respectively. Finally put forward relevant discussions and suggestions to make older people tourism more healthy and sustainable.